The Microphone Feedback Analogy for Chatter in Machining - Tony Schmitz (Shock and Vibration)
This paper provides experimental evidence for the analogy between the time-delay feedback in public address systems and chatter in machining. Machining stability theory derived using the Nyquist criterion is applied to predict the squeal frequency in a microphone/speaker setup. Comparisons between predictions and measurements are presented.